Characterisation of foot clearance during gait in people with early Parkinson׳s disease: Deficits associated with a dual task. Issue 13 (6th September 2016) - Alcock, Lisa; Galna, Brook; Lord, Sue; Rochester, Lynn
Abstract: Tripping is a common cause of falls in older adults and people with Parkinson׳s disease (PD). Foot clearance during gait may be impaired when distracted by a dual task and thus inform trip risk. This study aimed to evaluate whether foot clearance is impaired in PD and is adversely affected by a dual task. 81 older adults and 76 PD walked at a comfortable pace for two minutes under single and dual task conditions (digit recall). Temporal spatial gait was measured using an instrumented walkway. Heel and toe trajectories were obtained bilaterally using 3-dimensional motion capture. Foot clearance was reduced in PD ( p <.001) and under dual task ( p <.027). The take-off (toe) gradient was reduced under dual task irrespective of group and the landing (heel) gradient was reduced in PD irrespective of task ( p <.001). An increased proportion of unimodal toe distributions were observed for PD, particularly under dual task. Group differences were retained when controlling for step length (landing gradient and peak toe clearance in late swing) and gait velocity (landing gradient). Distinct differences in foot clearance were observed even in the early clinical stages of PD. Dual tasking may increase trip risk due to insufficient toe clearance (early swing) for both older adults and PD. Inadequate heel clearance (late swing) may increase falls risk in PD. Clearance deficits in PD are partially related to a reduced gait velocity and step length which may be targeted in tailored therapies. Further work is necessary to understand the mechanisms underlying this pathology-associated deficit.